1985
DOI: 10.1093/oxfordjournals.jbchem.a135397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of β-Glucan Structures in a Cell Wall Mutant of Saccharomyces cerevisiae and the Wild Type

Abstract: A mutant of Saccharomyces cerevisiae defective in the cell wall beta-glucan structure was obtained. The mutant cells are extremely sensitive to (beta 1-3)-glucanase digestion and mild alkali treatment. Structural analysis revealed that the alkali-insoluble, skeletal glucan from wild type cells contains two components, a (beta 1-3) linked glucan with a laminated structure, and a highly branched glucan containing predominantly (beta 1-6) linkages. The mutant cells lack the latter component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We have not precisely analyzed the nature of the linkages of the P-glucan fractions from the mutant strains; therefore, we cannot rule out the possibility that small changes in the length of the (1-3)p-linked glucose chains or small differences in the degree of (1-6)p crosslinking possibly affect the secondary and tertiary conformation of the 3-glucan and, ultimately, the nature of the network structure in the cell wall and the shape of the cell. In fact, some authors (11,28) favor the hypothesis that the number of (1-6)1-glycosidic linkages is a key element in controlling the hydrodynamic properties and morphology of the yeast cell wall. Indeed, very recently (1,18) Bussey and coworkers clearly showed the role of (1-6),B-D-glucan in cell morphology and cell growth in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not precisely analyzed the nature of the linkages of the P-glucan fractions from the mutant strains; therefore, we cannot rule out the possibility that small changes in the length of the (1-3)p-linked glucose chains or small differences in the degree of (1-6)p crosslinking possibly affect the secondary and tertiary conformation of the 3-glucan and, ultimately, the nature of the network structure in the cell wall and the shape of the cell. In fact, some authors (11,28) favor the hypothesis that the number of (1-6)1-glycosidic linkages is a key element in controlling the hydrodynamic properties and morphology of the yeast cell wall. Indeed, very recently (1,18) Bussey and coworkers clearly showed the role of (1-6),B-D-glucan in cell morphology and cell growth in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some important studies have been performed with S. cerevisiae mutants altered in the biosynthesis of other cell wall polymers such as mannan (4,15) or chitin (2,29). Although P-D-glucan is assumed to be essential for yeast cell integrity, very few studies have been done with ,B-glucan mutants (11,20,28), and most of them refer to the (1-6),3-D-glucan from S. cerevisiae. A recent study of KRE genes, involved in killer factor resistance (1,18), has provided the first evidence for a pathway of (1-6)-p-D-glucan synthesis and cell wall ,3-glucan assembly in S. cerevisiae.…”
mentioning
confidence: 99%
“…In fact, only a few linear (1 6)-β-glucans have been identified, the best known being pustulan from Umbilicaria species [2] and lutean from Penicillium luteum [3]. However, (1 6)-β-linkages occur frequently in the glucans of yeast and filamentous-fungal cell walls [4][5][6][7][8][9] and, not surprisingly, enzymes hydrolysing (1 6)-β-glucosidic linkages are common in these organisms [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Genes that are involved in (1,3)-3-glucan synthesis, however, remain largely unknown. Enzymatic studies revealed that the (1,3)-p-glucan synthase is likely to be a membrane-associated protein regulated by a G protein (11,30), and mutants with reduced levels of (1,3)-p-glucan have been isolated and characterized (28,48,57). We report here the cloning and characterization ofKNR4, a gene involved in (1,3)-,B-glucan biosynthesis.…”
mentioning
confidence: 97%